RANCANG BANGUN SISTEM INFORMASI PENJUALAN PADA PERCETAKAN NUSA JAYA BERBASIS WEB - Susanto, Budi; Adnyana, I Ketut Widhi; Laxsmi, Ni Putu Ayu Puspa (INTI TALAFA: Jurnal Teknik Informatika, 2019)
Printing Nusa Jaya is one of the businesses engaged in services. In order of receipt, it is still recorded conventionally by the printed party on a book and stored in document form as an archive. Searching for customer data is often a problem. In this case required a computerized sistem to facilitate the process of searching data. This study aims to build a web-based sales information sistem Nusa Jaya, using the programming language PHP and MySQL database. Sales information sistem is expected to help solve existing problems, can provide the right solution in finding customer data using computerized sistem. The test results using blackbox testing and try the sistem in accordance with the completion of this final task is the manufacture of sales information sistem in print Nusa Jaya. Keywords: sales information sistem